O ensino das relações topológicas com crianças dos anos iniciais do ensino fundamental I - Chiapetti, Dulcinéia Cristina (2018)
This master thesis about “The teaching of topological relationship with children from the first years of Elementary School I" focuses on the difficulties that the child presents in the learning process, mainly, in the formation of concepts that involve the laterality, the cardinal directions and the other guiding principles. It is justified by the fact that many children present difficulties to understand the topological relationship and to relate the laterality directions to the cardinals (right / East, left / West, front / North and back / South). Also by the difficulty to teaching Geography in the children education and, consequently, by the lack of importance given to the geographic contents. The text approach the Theory of Activity proposed by Leontiev, because it supports the foundations of the relationship between those who teach and those who learn. It explains the process of construction concepts and the apprehension of certain activities realized in the school context. Another basis is in Vygotsky because he proposes the emphasis on action and learning as a process that occurs from outside to into and is full of historicity. Also by the context that those who teaches is the mediator of the process. Another theorist is Lúria that defends the activities in the concrete context, to enable to pass to the abstract categories. This research of a methodological nature, a case study, is based on Yin (2001). The data collection was based on interviews with 114 children between five (5) and six (6) years; five (5) teachers; one (1) coordinator. It was realized in four (4) municipal schools from Itapejara D’Oeste/PR. The interviews were conducted individually and 39 activities were done, four (4) individual and thirty five (35) in the collective. It enabled a space for discoveries of teaching methodologies that, through them, teachers can teach important geographical concepts. It identifies the importance of considering the individuality of the child to investigate the difficulties presented by this child. The didactic sequences give the children the opportunity to participate in the construction of knowledge, show the importance of pedagogical work related to the geographical concepts of: laterality, cardinal directions, also, to work the cartographic representations. If the child presents difficulty during the formation of these concepts is because the process is still in progress. The child needs to have the knowledge associated with something that is part of his daily life, mainly in terms of cardinal directions and spatial references. When the child does not understand the relationship between the concepts North / Front, South / Back, East / Right and West / Left, it is difficult for the child to orient or locate himself in space and even understand what these concepts are for.